Application of Glass Transition in Food Processing. Issue 6 (25th April 2016) - Balasubramanian, S.; Devi, Apramita; Singh, K. K.; Bosco, S. J. D; Mohite, Ashish M.
Abstract : The phenomenon of glass transition has been employed to food products to study their stability. It can be applied as an integrated approach along with water activity and physical and chemical changes in food in processing and storage to determine the food stability. Also associated with the changes during agglomeration crystallization, caking, sticking, collapse, oxidation reactions, nonenzymatic browning, and microbial stability of food system. Various techniques such as Differential Scanning Calorimetry, Nuclear Magnetic Resonance, etc. have been developed to determine the glass transition temperature (Tg ) of food system. Also, various theories have been applied to explain the concept of Tg and its relation to changes in food system. This review summarizes the understanding of concept of glass transition, its measurement, and application in food technology.